2020
DOI: 10.1155/2020/8978704
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Attenuates Hypoxia-Induced Inflammation in BV2 Microglia by Inhibiting Oxidative Stress and NF-κB/Hif-1α Signaling

Abstract: Hypoxia-induced neuroinflammation typically causes neurological damage and can occur during stroke, neonatal hypoxic-ischemic encephalopathy, and other diseases. Propofol is widely used as an intravenous anesthetic. Studies have shown that propofol has antineuroinflammatory effect. However, the underlying mechanism remains to be fully elucidated. Thus, we aimed to investigate the beneficial effects of propofol against hypoxia-induced neuroinflammation and elucidated its potential cellular and biochemical mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Although propofol is typically used as an anesthetic agent, it also functions to eliminate inflammation. Propofol reduces both the gene and cytokine productions of TNF- α in not only CoCl 2 -treated hypoxic BV2 microglia but also cecal ligation and puncture-administrated rat liver [ 16 , 17 ]. In this study, RAW 264.7 cells were pretreated with or without propofol (10 or 25 μ g/ml) followed by infected with DENV for 24 h. ELISA analysis showed that DENV infection significantly increased mouse TNF- α production; however, propofol treatment reduced the cytokine levels in a dose-dependent manner ( Figure 5(a) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although propofol is typically used as an anesthetic agent, it also functions to eliminate inflammation. Propofol reduces both the gene and cytokine productions of TNF- α in not only CoCl 2 -treated hypoxic BV2 microglia but also cecal ligation and puncture-administrated rat liver [ 16 , 17 ]. In this study, RAW 264.7 cells were pretreated with or without propofol (10 or 25 μ g/ml) followed by infected with DENV for 24 h. ELISA analysis showed that DENV infection significantly increased mouse TNF- α production; however, propofol treatment reduced the cytokine levels in a dose-dependent manner ( Figure 5(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the modulation of cellular inflammation through suppressing COX activity in macrophages, propofol attenuates neuroinflammation. Peng et al found that propofol treatment blocks NF- κ B/Hif-1 α signaling and reduces the gene expressions and cytokine secretions of TNF- α , IL-1 β , and IL-6 in hypoxic BV2 microglia [ 16 ]. Propofol treatment also could remarkably inhibit gene expressions of TNF- α , TLR-4, CD14, and GM-CSF in cultured hepatocytes under LPS stimulation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is widely used as an anesthetic and it has been reported to possess anti-inflammatory properties ( 27 ). A previous study identified its role in alleviating inflammation via the inhibition of the NF-κB signaling pathway in allergic asthmatic mice; however, whether it could play a central role in suppressing the NF-κB signaling pathway to reduce inflammation and cell apoptosis remains unclear ( 28 ). In the present study, pretreatment with propofol increased cell viability, reduced apoptosis and ameliorated inflammation by inactivating the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Intense studies have revealed that propofol can regulate a plethora of genes related to the activation of microglia [19,[32][33][34]. Previously, we reported that propofol attenuates hypoxia-induced neuroinflammation, at least in part by inhibiting oxidative stress and NF-κB/hypoxia inducible factor-1α (Hif-1α) signaling in BV2 microglia [35]. However, the knowledge of the roles of miRNAs on propofol-induced inactivation of microglia is limited [18].…”
Section: Discussionmentioning
confidence: 99%
“…miR-221/222 expression can be downregulated by propofol in a dosedependent manner. Interestingly, propofol is sufficient to inhibit several inflammatory signaling pathways, such as NF-κB, p38 MAPK, and JAK1/STAT3 pathway [35][36][37]. Thus, it will be interesting to investigate whether the inactivation of these inflammatory signaling pathways by propofol is responsible for the decrease in the expression of miR-221/222 in microglia.…”
Section: Discussionmentioning
confidence: 99%